Consumer perception of food attributes - Matsumoto, Shigeru; Otsuki, Tsunehiro (CRC Press, 2021)
"Where does food come from? How is food produced? Today, consumers are concerned with numerous attributes of food such as these. Cruelty to animals, food contamination and safety, fair trade practice, genetic modification, organic farming, geographical origin, and sustainability are important attributes. It is important for policy makers, producers, and retailers to understand how consumers value these attributes. This book summarizes empirical findings on consumer valuation of food attributes from various scholarly works, reviews steps taken to meet consumer demand for food credence attributes and also discusses the need to strengthen communication between producers and consumers"...